Covid-19, institutional responses and the role of climate : a comparative study between Côte d'Ivoire and other West African countries - (:unkn) unknown (My University, 2022)
This paper analyzes Côte d'Ivoire's institutional response to the spread of Covid-19 and explores the measures beyond political control, especially the impact of environmental variations, by comparing the Ivorian case to other West African countries, to deconstruct misconceptions about the propagation of Covid-19 in Africa and suggests a rereading of Africa's place in the collective imaginaries, including at the scientific level.The approach uses political science, which pays particular attention to national political trajectories in relation to institutional responses to the Covid-19. In the subtitle of his book, American political historian Peter Baldwin (2021) asks the question that runs through our contribution: 'Why has the fight against the coronavirus been so different around the world?' Our approach to the problem, based on a broadly defined multifactorial one, attempts to refine the overly encompassing factors, putting each of the empirical factors into a national, or in Côte d'Ivoire's case, even a local context. The lockdown imposed by the authorities on Abidjan (Côte d'Ivoire's capital) from March 26 to July 15, 2020, for example, was a major event in the country's response to the Covid-19 pandemic. The paper is borne out of our transdisciplinary research (in political science, sociology, climatology, meteorology, atmospheric physics, and oceanography) presented at the West African Consortium for Clinical Research on Epidemics Pathogens (WAC-CREP, 2022) international symposium in March 2022 in Yamoussoukro.
Keywords: African Research